Leveraging finance capital: Urban change and self-empowerment of real estate developers in India. (May 2016) - Rouanet, Hortense; Halbert, Ludovic
This paper questions the effects of the financialisation of Indian real estate markets with a focus on the Bangalore city-region. Research on Southern cities has concluded that globally connected but locally embedded real estate developers contribute to anchoring transnational investment. Yet, the acknowledged dearth of studies on the real estate industry in post-liberalisation India limits our understanding of the ongoing empowerment of local urban actors, including developers. Adopting a cultural political economy perspective, the paper analyses how developers leverage finance capital to achieve greater economic and political agency and thus contribute to the material, symbolic and political transformations of cities. It first demonstrates that finance capital has sustained Bangalore-based developers' growth strategies throughout Southern India. Subsequently, developers shape the materialities of metropolises via a piecemeal juxtaposition of medium-sized developments. Although this may occasionally meet government strategies for modernising their cities, it more often than not constitutes an understudied obstacle to States' mega-projects that are outdone by developers' ability to work through the intricacies of local land markets and bureaucracies. Furthermore, having become dominant city-builders, developers are in a situation to circulate representations concerning what the desirable city should be. Such narratives aim at inserting local real estate markets into globalising financial commodity chains while also legitimating developers' own role. Consequently, developers attempt to promote – with some success – prescriptions in favour of State reforms and the adoption of pro-urban growth policies. The ongoing financialisation of urban production thus participates in the self-empowerment of developers in India's cities.